Assessing Seismic Behavior in RC Buildings with Varied Vertical Aspect Ratios: A Comparative Study (International Journal of Scientific Research and Management (IJSRM), 2023)
Limited space in cities due to urbanization and population growth has given rise to tall and distinctively designed buildings. This study focuses on how a building’s vertical aspect ratio (height-to-width ratio) affects the seismic performance of residential concrete buildings. In earthquake-prone Nepal, seismic analysis is crucial for buildings in high-risk areas. We investigated the impact of vertical aspect ratio and the presence of masonry infills and soft stories in reinforced concrete frame buildings. Rectangular base models were analysed at 3, 5, and 7 stories. These models were categorized into bare frames, infill frames, and infill frames with soft stories at the ground level. Linear analysis, non-linear analysis, and design of the building have been performed as per the relevant Indian codes of practice. The effect of infills on dynamic characteristics, yield patterns and capacity has been studied with the help of Non-Linear Analysis. The result of the analysis indicates that the structures have lesser capacity and higher drift with the increase in vertical aspect ratio. It also has been observed that infills contribute to a large increase in the stiffness and strength of the structure, so the deformation capacity of the structure gets reduced.